A case of arteriovenous fistula of left mandibular ramus. Issue 6 (November 2022) - Kato, Yuta; Hayashi, Yutaro; Fukaya, Eri; Ogawa, Chikara; Sugita, Miki; Masumoto, Kazuma
Abstract: Arteriovenous fistula (AVF) is a condition in which arteries and veins are short-circuited without passing through capillaries, and veins dilate owing to increased pressure, forming varicose veins. However, these lesions are rare in the head and neck. In this paper, we report a case of AVF of the left mandibular ramus. A 22-year-old female was referred to our department for investigation and treatment of left cheek pain and trismus. No obvious swelling was observed on the left cheek, and bruit and pulsation were observed over the left mandible. Slight swelling was observed inside the oral cavity at the gingiva of the distal part of the left mandibular third molar. On computed tomography, dilation of the maxillary artery and inferior alveolar artery from the left external carotid artery were recognized. Moreover, AVF and mandibular scalloping were observed near the left mandibular foramen. Transarterial vascular embolization was performed because AVF formation and shunts between the submental artery, inferior alveolar artery, and external jugular vein were observed on angiography. After the operation, bruit and pulsations in the left mandibular region disappeared, and the left cheek swelling and trismus improved.